Solitary eccrine syringofibroadenoma - Case Report - Caroline Bertolini Bottino; Tais Ferreira Guimarães; Flávio Rezende Gomes; Antonio Macedo D'Acri; Ricardo Barbosa Lima; Carlos José Martins (Sociedade Brasileira de Dermatologia, 2015)
AbstractEccrine syringofibroadenoma is a rare benign adnexal neoplasm derived from cells of the acrosyringium of eccrine sweat glands. ESFA usually manifests as a solitary nodule on the extremities of elderly patients, but it may also present as papules, nodules or plaques. Its clinical appearance is nonspecific and malignant neoplasms should beconsidered in the differential diagnosis. However, histopathological findings are typical. The main treatment is surgical excision. In order to illustrate a typical presentation of the tumor, we report a case of solitary eccrine syringofibroadenoma, including the surgical treatment used and its result.